Pengaruh Latihan Circle Passing dan Y Passing Pattern Terhadap Akurasi Passing Pemain Sepak Bola SSB Mitra Sampangan U-12 - Vicky Tri Firmansyah; Martin Sudarmono; Mohamad Annas; Fery Darmanto (Universitas Negeri Semarang, 2024)
This study aims to determine the effect of Circle Passing and Y Passing Pattern training on the passing accuracy of SSB Mitra Sampangan U-12 players. This type of research is quantitative research with experimental methods. The design of this research is